Penggunaan Larutan Pepaya (Carica papaya) sebagai Larvasida Nyamuk Aedes aegypty - Restu Prastiwi; Anita Dewi Moelyaningrum; Prehatin T. N (Universitas Serambi Mekkah, 2019)
Aedes aegypti mosquito is a type of mosquito that can carry dengue virus that causes dengue fever. This mosquito has the potential to transmit dengue hemorrhagic fever (DHF). DHF is a disease characterized by sudden fever, bleeding both on the skin and in other parts of the body and can cause shock and death. So in order to reduce the impact of the disease, there are several ways that must be taken. One way of controlling that is done to reduce the population of aedes aegypti mosquitoes is by reducing larval growth by using a solution of papaya leaves as larvacide. Papaya leaves contain tannins of 0.12%. So it is possible to kill larvae. The purpose of this study was to analyze the differences in the average mortality of untreated instar 1 aedes aegypti larvae and treated with a solution of distilled papaya leaves, amounting to 0ml / 100ml (X0), 1ml / 100ml (X1), 2ml / 100ml (2) , 4ml / 100m (X3) with observations every 6 hours for 24 hours. This study is a true experimental study with the presentation of the data analyzed using the kruskal wallis test on spss. The results showed that there were differences between the control group and the treatment group (p 0.05). The most significant difference occurred in the 4ml / 100ml (X3) group which had the highest mortality than the other groups. So the higher the concentration and the longer the duration of exposure, the higher the mortality rate in the larvae.